Post-WWII modernism with a glaze: A comparison between Antwerp and Lisbon - Vos, E.; Geerinckx, S.; Rodrigues, I. L.; Milheiro, A. V. (Docomomo Journal, 2023)
Post World War II European modern housing often exhibited a Corbusian influence, but Le Corbusier was not embraced to the same extent everywhere, as noticed during exchanges between the University of Lisbon and the University of Antwerp in the ambit of the COST-Action 18137 on MCMH. While Belgium has several 1950s social housing projects, strongly indebted in its Unité d’habitation in Marseilles, Portugal does not. There, social housing architecture remained rather conservative, even though Corbusian features manifested themselves in some middle-class mass housing projects, such as the complex on Avenida Estados Unidos da América in Lisbon (1954-1966) designed by Lucínio Cruz, Alberto Ayres de Sousa and Mário Oliveira. While the housing blocks are on pilotis, they also have notable Art-Deco elements. In Belgium, free-standing modernist housing on pilotis with Art-Deco features also appears, such as the housing project at the Jan De Voslei in Antwerp designed by Jos Smolderen (1952-1967). These Modernist/Art-Deco hybrids have never been explored in depth because they are considered not radical enough. However, these cases shed light on how (older) architects mediated between traditional architecture and Modernism, between their own preferences and those of the state or housing company. They illuminate the political, social, and urban context in which these buildings were created. This paper explains why the principles Belgian architects applied to social housing were closer to Lisbon’s middle-class housing than their similar buildings for low-income housing. Based on cross-referencing archival material, legislation, on-site observations, and a study of the political, urban and social context, this paper posits a re-reading of Le Corbusier’s legacy in middle-class housing in Lisbon versus Antwerp.